Jackaroo - Voigt, Cynthia (New York : Scholastic, 1995)
When hard times among the People revive the old stories of the hero Jackaroo, an innkeeper's daughter follows her own quest to unlock the secret reality behind the legend.
Originally published: New York : Atheneum, 1985.
840
Cynthia Voigt is a Maine author. She has been a resident of Deer Isle since the 1990s.
Keywords: Heroes -- Fiction